A FATAL CASE OF BILATERAL INTERSTITIAL PNEUMONIA (BLIP): INTERFERON ALPHA 2 A INDUCED. - o, Balaji; kl, Bairy; Priya d, Amita; Thomas, Joseph; Patil, Navin (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Adult T-cell leukemia/lymphoma (ATLL) is a rare lymph proliferative disorder of mature CD4 T-cells caused by the human T-lymph tropic type 1 (HTLV 1) of retrovirus family. Combination of zidovudine and interferon Alfa combination is one of most commonly used regimen. Many drugs are implicated in causing interstitial lung disease. Hence, we report a case of interferon Alfa-induced bilateral interstitial pneumonia in a 32-year-old female patient diagnosed with ATLL with HTLV 1 positivity.